Commentary: New Directions in the Study of PRC-Era Science. Issue 3 (1st September 2019) - Ghosh, Arunabh
Abstract: This essay offers commentary on the previous three articles regarding PRC-era science by Sarah Mellors, Chuan Xu, and Sigrid Schmalzer. It notes that by moving beyond older concerns that were centered on issues of state control or techno-nationalism, these articles exemplify new directions in the study of PRC-era science. Their focus on lived experience, local stories, and materiality provides rich and diverse perspectives on histories of science in the PRC by exposing the often contradictory ways in which the power and influence of science operated across society. The commentary concludes by identifying three pathways for future research.